2022
DOI: 10.1038/s12276-022-00804-1
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine-targeting compounds as a new treatment strategy for diabetic wounds via inhibition of the histone methyltransferase SET7/9

Abstract: In hypoxia and hyperglycemia, SET7/9 plays an important role in controlling HIF-1α methylation and regulating the transcription of HIF-1α target genes, which are responsible for angiogenesis and wound healing. Here, we report the Ir(III) complex Set7_1a bearing acetonitrile (ACN) ligands as a SET7/9 methyltransferase inhibitor and HIF-1α stabilizer. Interestingly, Set7_1a could engage SET7/9 and strongly inhibit SET7/9 activity, especially after preincubation with homocysteine (Hcy), which is elevated in diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The FDA has approved bioengineered skin-care products such as Apligraf and Dermagra for treating diabetic foot ulcers (DFU). 28 FG-2216 is in clinical trials (IOX3), an effective and orally active inhibitor of HIF-1a prolyl hydroxylase-2 (PHD2) with an IC50 of 3.9 M. In vivo, FG-2216 produces high levels of erythropoietin and low levels of haemoglobin. 29 Previous research has demonstrated that hyperglycaemia inhibits HIF-1a ′ s activity in diabetic mice by destabilizing it through a VHL-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The FDA has approved bioengineered skin-care products such as Apligraf and Dermagra for treating diabetic foot ulcers (DFU). 28 FG-2216 is in clinical trials (IOX3), an effective and orally active inhibitor of HIF-1a prolyl hydroxylase-2 (PHD2) with an IC50 of 3.9 M. In vivo, FG-2216 produces high levels of erythropoietin and low levels of haemoglobin. 29 Previous research has demonstrated that hyperglycaemia inhibits HIF-1a ′ s activity in diabetic mice by destabilizing it through a VHL-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The excitation and emission wavelength were set at 320 and 405 nm, separately. The data was analyzed with Graphpad prism 9.0 and all experiments were performed in triplicates [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Proangiogenic factor expression is another thing that HMTs can influence. For instance, in hypoxic and hyperglycemic conditions, SET7/9 can methylate HIF-1α at lysine residue 32 and suppress the levels of hypoxia-inducible factor-1α (HIF-1α), which delays the healing of wounds [ 72 ]. Enhancer of zeste homolog 2 (EZH2), on the other hand, can stimulate HIF-1α H3K4me3 to raise HIF-1α expression, improve wound repair in diabetic rats wounds, and increase dermal fibroblast viability [ 73 ].…”
Section: Epigenetic Modification In Diabetic Wound Healingmentioning
confidence: 99%